Analysis and Research on Anti-Condensation Performance of Molten Salt Control Valve - Zhang, Jiabin; Sun, Zegang; Zhang, Zhonghao (International Journal of Mechanical and Electrical Engineering, 2025)
During the molten salt flow process in the molten salt control valve, localized temperatures may fall below the solidification point of the molten salt, leading to partial solidification within the valve body and consequently affecting the flow performance of the valve. This study conducts temperature and flow field simulations under various operating conditions to investigate the potential occurrence of solidification during the molten salt flow process. Specifically, it analyzes whether the molten salt temperature drops below its solidification point under three extreme scenarios: fully open valve position, sudden valve closure with residual molten salt remaining in the valve body, and abrupt flow interruption due to pipeline equipment failure. The research findings demonstrate that molten salt solidification does not occur in any of these three scenarios, providing valuable reference data for subsequent optimization design of molten salt control valves.